2017
DOI: 10.4306/pi.2017.14.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Depression and Laryngopharyngeal Reflux

Abstract: This study investigated the relationship between depression, somatization, anxiety, personality, and laryngopharyngeal reflux (LPR). We prospectively analyzed 231 patients with symptoms with LPR using the laryngopharyngeal reflux symptom index and the reflux finding score. Seventy nine (34.2%) patients were diagnosed with LPR. A significant correlation was detected between the presence of LPR and total scores on the Patient Health Questionnaire-9 (5.6±5.3 vs. 4.0±4.6, p=0.017) and the 7-item Generalized Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The sensation of sticking in the throat can appear continuously so that it can cause psychological disorders. [15][16][17] The results showed that there was no significant association between risk factors as gender, age, duration of symptoms, BMI, smoking and diet with psychiatric symptoms: depression, anxiety and stress. In another study also reported that there was no relationship between gender, age, BMI, and smoking habits and the patient's quality of life for LPR.…”
Section: Discussionmentioning
confidence: 92%
“…The sensation of sticking in the throat can appear continuously so that it can cause psychological disorders. [15][16][17] The results showed that there was no significant association between risk factors as gender, age, duration of symptoms, BMI, smoking and diet with psychiatric symptoms: depression, anxiety and stress. In another study also reported that there was no relationship between gender, age, BMI, and smoking habits and the patient's quality of life for LPR.…”
Section: Discussionmentioning
confidence: 92%
“…One-third of LPR patients have anxiety and a significant reduction in social activities. 24 Patients with LPR have a significant increase in anxiety scores with Hospital Anxiety and Depression Scale (HADS). Patients might have anxiety over significant pathology, chronic nature of the disease, and lumps in their throat and are concerned about this symptom, whether it is an early sign of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, laryngopharyngeal reflux symptoms, including cough, sore throat, and globus pharyngeus, may appear as a result of autonomic dysfunction, and are similar to the early symptoms of COVID-19. 23,24 Thus, it is possible that the incidence of patients with symptoms was high because there were many symptoms similar to COVID-19 symptoms resulting from the influence of psychological factors.…”
Section: Discussionmentioning
confidence: 99%